2012
DOI: 10.1136/bcr.05.2011.4289
|View full text |Cite
|
Sign up to set email alerts
|

Chiari network: a protective filter against pulmonary embolism in a case of polycythaemia

Abstract: The Chiari network, a net-like structure within the right atrium, has been described as an embryonic remnant of no clinical significance. Its role in facilitating paradoxical arterial embolic events and as a potential site for thrombus formation however, has been reported in the literature. This case illustrates the protective filter-effect of the Chiari network in a 79-year-old Caucasian man with an unknown diagnosis of polycythaemia rubra vera who presented with clinical signs and symptoms of deep vein throm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…It may act as a nidus for thrombus formation as well as a protective filter against pulmonary embolism. Obaji et al reported that the Chiari network may play a protective role such as inferior vena cava filter in the case of polycythemia [ 4 ]. However, Schneider et al emphasized significantly higher prevalence rates for patent foramen ovale in patients with a Chiari network and an association with a serious risk for arterial embolism [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…It may act as a nidus for thrombus formation as well as a protective filter against pulmonary embolism. Obaji et al reported that the Chiari network may play a protective role such as inferior vena cava filter in the case of polycythemia [ 4 ]. However, Schneider et al emphasized significantly higher prevalence rates for patent foramen ovale in patients with a Chiari network and an association with a serious risk for arterial embolism [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of Chiari's network is reported to be approximately 2% with estimates varying from 1.3 to 4% in postmortem findings and 0.3 to 9.5% in TTE findings [ 1 ]. The previously reported clinical complications associated with Chiari's network are the intra-RA thrombus formation [ 3 ] as well as the entrapment of thromboemboli [ 4 ], atrial tachyarrhythmia [ 5 ], and device entrapment [ 6 12 ]. To date, 9 cases of device entrapment with Chiari's network have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Still in debate, chiari network may have a protective role in preventing embolization by holding thrombus in the network in some patients with Thrombophilia. 10 …”
Section: Discussionmentioning
confidence: 99%